Using bank loans as collateral in Europe: The role of liquidity and funding purposes - François Koulischer; Patrick Van Roy (National Bank of Belgium, 2017)
We show that illiquid assets such as bank loans are used by euro area banks both as central bank collateral for short-term liquidity insurance purposes and for longer-term funding purposes for issuing covered bonds or asset-backed securities. We then explore the determinants of the choice of using bank loans for short-term liquidity insurance purposes or long-term funding purposes focusing on the case of Belgian banks. We find that (1) loan types are key to alleviating asymmetries of information; (2) regulatory requirements play a major role in the choices of banks, both directly and indirectly through clientele effects and (3) there are significant switching costs between the various uses of bank loans as collateral so historical decisions also determine the use of bank loans as collateral.
Keywords: E52; E58; G01; F36; 330; Collateral; securitisation; bank loans; liquidity